BS EN ISO 6888-1. Microbiology of the food chain. Horizontal method for the enumeration of coagulase-positive staphylococci (Staphylococcus aureus and other species). Part 1. Technique using Baird-Parker agar medium (17th March 2020) - British Standards Institution,
No abstract available